Beyond Linearity – An Analysis of the Interdependencies across the Customer Journey - Christian Duncker; Jens K. Perret (Research Journal for Applied Management (RJAM), 2022)
This study analyzes the various stages of the customer journey (CJ) concept using the example of the lingerie product area. The fields of Customer Journey Management, Customer Relationship Management, and Customer Experience Management, which have so far been largely considered separately, are summarized into a comprehensive framework. In the second part, the study uses a representative survey of 1,050 women of generation X to establish the validity of the model empirically. It additionally analyzes in how far the data requires the expansion of the model by a secondary vertical meta-level to capture interlinkages not considered within a purely linear model of the CJ. The result, a two-dimensional network structure of the CJ, illustrates the links between different parts of the CJ and the requirement of a multidimensional approach towards the customer journey. Finally, the study presents an approach on how to model the willingness-to-pay as the central part of the CJ by implementing an artificial neural network (ANN) approach. The results show the ANN is ideally suited for such a complex background. The resulting model combines high explanatory power with the potential to increase it further by successively including newly available customer data, thus offering additional benefits for practitioners.
Keywords: 650; Customer journey; CRM; customer experience; artificial neural network; survey data